(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
The present study was undertaken with the aim of investigating the bacteriological quality of locally available raw, pasteurized and UHT milk in Gazipur District. A total 5 raw, pasteurized and UHT milk samples were collected during November to December 2016. All the pasteurized and UHT milk samples showed the total aerobic heterotrophic bacterial (TAHB) level above the standard acceptable range (i.e. > 104 cfu/ml for pasteurized milk and > 0 for UHT milk). Both Gram positive and Gram negative pathogenic bacteria viz. Staphylococcus aureus, S. epidermidis, Bacillus sp., Pseudomonas sp. and Enterobacter sp. were isolated from studied samples. API 20 E was used for confirmation of Pseudomonas sp. This study indicates that most of the pasteurized and UHT milk samples were not satisfactory in terms of public health standard. Therefore, care must be taken to avoid possible health risk in every step involving collection, transportation, storage and post pasteurization handing of raw milk. Jahangirnagar University J. Biol. Sci. 7(2): 13-19, 2018 (December)